Phytochemicals: Potential Lead Molecules for MDR Reversal - Boshra Tinoush; Iman Shirdel; Michael Wink (Frontiers Media S.A., 2020)
Multidrug resistance (MDR) is one of the main impediments in the treatment of cancers. MDR cancer cells are resistant to multiple anticancer drugs. One of the major mechanisms of MDR is the efflux of anticancer drugs by ABC transporters. Increased activity and overexpression of these transporters are important causes of drug efflux and, therefore, resistance to cancer chemotherapy. Overcoming MDR is a fundamental prerequisite for developing an efficient treatment of cancer. To date, various types of ABC transporter inhibitors have been employed but no effective anticancer drug is available at present, which can completely overcome MDR. Phytochemicals can reverse MDR in cancer cells via affecting the expression or activity of ABC transporters, and also through exerting synergistic interactions with anticancer drugs by addressing additional molecular targets. We have listed numerous phytochemicals which can affect the expression and activity of ABC transporters in MDR cancer cell lines. Phytochemicals in the groups of flavonoids, alkaloids, terpenes, carotenoids, stilbenoids, lignans, polyketides, and curcuminoids have been examined for MDR-reversing activity. The use of MDR-reversing phytochemicals with low toxicity to human in combination with effective anticancer agents may result in successful treatment of chemotherapy-resistant cancer. In this review, we summarize and discuss published evidence for natural products with MDR modulation abilities.